On the Measurement of the (Non)linearity of Costas Permutations - Konstantinos Drakakis (Journal of Applied Mathematics)
We study several criteria for the (non)linearity of Costas permutations, with or without the imposition of additional algebraic structure in the domain and the range of the permutation, aiming to find one that successfully identifies Costas permutations as more nonlinear than randomly chosen permutations of the same order.